PENGARUH KEGIATAN EKSTRAKURIKULER BAHASA JEPANG TERHADAP MINAT BELAJAR BAHASA JEPANG SISWA DALAM PROSES PEMBELAJARAN DI KELAS - Sherly Indah Permata; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research is a correlation study between Japanese language extracurricular activities (X) and a lot of learning (Y) using quantitative descriptive analysis techniques. In this study, there was a significant influence on Japanese language extracurricular activities on students' interest in learning Japanese in class. Where students who take part in Japanese language extracurriculars have a positive attitude during the learning process, such as being able to answer questions from the teacher, do assignments and are always present when learning Japanese in class.Key Words: Influence, Japanese language extracurriculars, interest in learning